Behaviour of reinforced concrete beam under dynamic loading / Azmi Aznan - Aznan, Azmi (Faculty of Civil Engineering, 1996)
The increase in use of high strength concrete (HSC) in modem construction is tremendously high. Thus its behaviour need to be understood clearly. The behaviour of high strength reinforced concrete beam (R.C Beam) under dynamic loading with respect to the serviceability and ultimate limits had been studied. Two R.C beams with minimum concrete strength of 60 N/mm2 tested, one to failure under static load, while another tested to 3,000,000 cycles under sinusoidal repeated load with mean load of 45 kN (50% of yield load equivalent to 38% of ultimate load). Investigation on deflections, ultimate loads and cracks width were done.